Exploring agroecology: a contextual analysis of Fatick, Senegal - Piraux, Marc; Lairez, Juliette; Richomme, Elodie; Fall, Modou Gueye; Anta Sall, Mame Cheikh,; Sourisseau, Jean-Michel; Cesaro, Jean-Daniel (2023)
Context assessment of the Agroecological Living Landscape (ALL) where the activities of the CGIAR Initiative on Agroecology are implemented. The All is situated in the Fatick department in the southeast of the groundnut basin.